Effectiveness of Chitosan Solution as Denture Cleanser to Inhibit the Growth of Candida albicans on Acrylic, Valplast and Luciton-FRS - Anindita Apsari; Vivin Ariestania (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: Heat cure acrylic and nylon thermoplastic valplast and lucitone-FRS brands are the three materials most often used as denture bases. Candida albicans is the dominant microorganism that can cause denture stomatitis. Cleaning denture can be done in two ways, namely the mechanical way with a toothbrush or an ultrasonic cleanser and a chemical method by immersing the denture into the cleaning solution. Chitosan solution is antibacterial and anti fungal which can inhibit the growth of Candida albicans colonies on heat cured acrylic plates, valplast and lucitone-FRS. Purpose: To determine the concentration of chitosan solution and the type of denture plate that most effectively inhibited the growth of Streptococcus mutans Candida albicans colonies on heat cured acrylic, valplast and lucitone-FRS plates. Materials and Methods: 21 heat cured acrylic plate samples, 21 valplast plate samples, 21 lucitone-FRS plate samples measuring 10x10x2 mm divided by 9 groups. Heat cured, valplast and lucitone-FRS acrylic plate samples were contaminated with Candida albicans then immersed using the concentration of 0.25%, 0.5% chitosan solution and sterile aquades as the control group with 90 minutes immersion time. The entire study sample was calculated using Candida albicans colonies on Sabourroud's Dextrose Agar media. Results: The Kruskall Wallis test showed a significant difference (p <0.05) in all treatment groups. Mann-Whitney showed a significant difference (p <0.05) in all groups in the Candida albicans study. Conclusion: Soaking the lucitone-FRS plate in 0.5% chitosan solution for 90 minutes was the most effective in inhibiting the growth of Candida albicans colonies.